Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B; Colombaroli, D; Chapron, E; Leroux, A; Tinner, W; Magny, M (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)